Alternative production method of Psilocybin, bioreactor cultivation of Psilocybe Cubensis - Hedlund,Petter (2025)
The scientific interest in psilocybin has recently been reignited, the research community has once again begun to investigate the promising potential that psilocybin offers in the area off treatment of depression and PTSD. An obstacle to the research of psilocybin is that today pharmaceutical grade psilocybin is produced using an inefficient and thus costly synthetic process. This hampers the research as the availability of the molecule is low and the price is high. By creating a cheaper or more efficient process, it is hoped that this may help encourage further research and clinical trials into psilocybin. Perhaps even a medical application in the future. This projects aim is to investigate the feasibility of liquid culture cultivation of Psilocybe cubensis for an industrial process. Similar processes are utilised today, for example in the production of citric acid which today is produced in submerged liquid cultures by Aspergillus niger. High Pressure Liquid Chromatography coupled to a Mass Spectrometer was employed for the separation and detection psilocybin in the fungal extracts. Due to the highly polar and zwitterionic nature of psilocybin separation proved to be difficult using a conventional C18 column. Hence other chromatography column formats were evaluated. Two mediums were tested during the project, potato dextrose broth and a defined minimal media. The potato dextrose broth produced significantly higher growth rates compared to the minimal media, yet no psilocybin could be definitively detected in the samples grown in it.
Keywords: psilocybin; bioreactor; HPLC; HPLC-MS; depression; mycelium; biotechnology